2012
DOI: 10.1002/etep.1677
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of arcing faults on overhead transmission lines for single-pole auto-reclosure

Abstract: SUMMARY To block auto‐reclosing operation for permanent earth faults on extra‐high‐voltage transmission lines, an accurate numerical algorithm is developed in this paper. The earth fault location and its nature (arcing or arc‐less) are estimated, only using the sequence quantities of the local terminal and their harmonics. The proposed algorithm calculates the amplitude of arc voltage and compares it with a given threshold value; then, decision is made if it is transient or not. A square wave arc model is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…There will be strong light and a high temperature, electromagnetic radiation, noise and other physical phenomena when an arc fault occurs, therefore, researchers are able to identify arc faults by detecting the occurrence of these physical phenomena [11][12][13]. Based on the features extracted from the electromagnetic radiation signal, least squares [14] and extreme learning machine [15] are used to identify arc faults by collecting the voltage signals in the circuit. However, the arc faults are very random and their locations are uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…There will be strong light and a high temperature, electromagnetic radiation, noise and other physical phenomena when an arc fault occurs, therefore, researchers are able to identify arc faults by detecting the occurrence of these physical phenomena [11][12][13]. Based on the features extracted from the electromagnetic radiation signal, least squares [14] and extreme learning machine [15] are used to identify arc faults by collecting the voltage signals in the circuit. However, the arc faults are very random and their locations are uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many algorithms designed to discriminate between transient and permanent faults, and to block auto‐reclosing operation for permanent faults, such as simple and accurate numerical algorithm proposed in Meyar‐Naimi et al, the most of the protection schemes in the field still relies on single‐pole tripping and reclosing (SPT&R). The algorithms for transverse differential protection using current samples from the past in calculation of directional element are analysed in this article together with their application with SPT&R. SPT&R is a well‐known and widely used technique for elimination of transient faults in high‐voltage networks.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have developed mathematical arc fault models such as an instantaneous arc model for a resistive-inductive system [ 19 , 20 ], a simplified arc fault model for analyzing and determining basic parameters [ 21 , 22 , 23 ], and an arc fault meta model of conductance [ 24 ]. Many studies have shown that arc faults exhibit some abnormal behaviors in terms of arc radiation, arc sounds, arc light, arc temperatures, arc currents and arc voltages in circuits [ 25 , 26 , 27 , 28 , 29 ]. When arc faults occur in circuits, the radiated electromagnetic signals increase in intensity and can be collected using a loop or stick antenna [ 25 ]; sounds and light from fault arcs appear and significantly increase in intensity [ 26 , 27 ]; and arc temperatures quickly increase to up to 13,000 K, with a large amount of heat being instantaneously released to the surrounding area [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…When arc faults occur in circuits, the radiated electromagnetic signals increase in intensity and can be collected using a loop or stick antenna [ 25 ]; sounds and light from fault arcs appear and significantly increase in intensity [ 26 , 27 ]; and arc temperatures quickly increase to up to 13,000 K, with a large amount of heat being instantaneously released to the surrounding area [ 14 ]. Fault arc voltages in transmission lines can be estimated through the least error squares method and can be used to identify arc faults [ 28 , 29 ]. However, mathematical arc fault models are usually used in theoretical analysis and simulations.…”
Section: Introductionmentioning
confidence: 99%